Identification of a 3′‐Untranslated Genetic Variant of RARB Associated With Carotid Intima‐Media Thickness in Rheumatoid Arthritis: A Genome‐Wide Association Study. Issue 3 (18th January 2019) - López‐Mejías, Raquel; Carmona, F. David; Genre, Fernanda; Remuzgo‐Martínez, Sara; González‐Juanatey, Carlos; Corrales, Alfonso; Vicente, Esther F.; Pulito‐Cueto, Verónica; Miranda‐Filloy, José A.; Ramírez Huaranga, Marco A.; Blanco, Ricardo; Robustillo‐Villarino, Montserrat; et al.
Abstract : Objective: To investigate the genetic background influencing the development of cardiovascular (CV) disease in patients with rheumatoid arthritis (RA). Methods: We performed a genome‐wide association study (GWAS) in which, after quality control and imputation, a total of 6, 308, 944 polymorphisms across the whole genome were analyzed in 2, 989 RA patients of European origin. Data on subclinical atherosclerosis, obtained through assessment of carotid intima‐media thickness (CIMT) and presence/absence of carotid plaques by carotid ultrasonography, were available for 1, 355 individuals. Results: A genetic variant of the RARB gene (rs116199914) was associated with CIMT values at the genome‐wide level of significance (minor allele [G] β coefficient 0.142, P = 1.86 × 10 −8 ). Interestingly, rs116199914 overlapped with regulatory elements in tissues related to CV pathophysiology and immune cells. In addition, biologic pathway enrichment and predictive protein–protein relationship analyses, including suggestive GWAS signals of potential relevance, revealed a functional enrichment of the collagen biosynthesis network related to the presence/absence of carotid plaques (Gene Ontology no. 0032964; false discovery rate–adjusted P = 4.01 × 10 −3 ). Furthermore, our data suggest potential influences of the previously described candidate CV risk loci NFKB1, MSRA, and ZC3HC1 ( P = 8.12 × 10 −4, P = 5.94 × 10 −4, and P = 2.46 × 10 −4, respectively). Conclusion: The present findings strongly suggest that genetic variation within RARB contributes to the development of subclinical atherosclerosis in patients with RA.